Adolescent Refusal of MMR Inoculation: F (Mother) v F (Father). Issue 4 (July 2014) - Cave, Emma
<x xml:space="preserve">Abstract</x> F (Mother) v F (Father) concerned a dispute between parents as to whether or not their 15 and 11 year old children should receive the MMR inoculation. Mrs Justice Theis took into consideration the wishes of both parents and the two 'intelligent, articulate and thoughtful' minors and held that inoculation was in their best interests. The troubled history of the MMR vaccine and its importance to public health provided the backdrop. Whilst the court's efforts to establish the views of the minors are to be commended, the decision is problematic in its assessment of the minors' individual medical interests and capacities, and in the significance placed on their views when determining whether inoculation would be in their best interests.